2021
DOI: 10.3389/fped.2021.794541
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell-Replete Versus ex vivo T-Cell-Depleted Haploidentical Haematopoietic Stem Cell Transplantation in Children With Acute Lymphoblastic Leukaemia and Other Haematological Malignancies

Abstract: Allogeneic haematopoietic stem cell transplantation (HSCT) represents a potentially curative option for children with high-risk or refractory/relapsed leukaemias. Traditional donor hierarchy favours a human leukocyte antigen (HLA)-matched sibling donor (MSD) over an HLA-matched unrelated donor (MUD), followed by alternative donors such as haploidentical donors or unrelated cord blood. However, haploidentical HSCT (hHSCT) may be entailed with significant advantages: besides a potentially increased graft-vs.-leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 106 publications
0
7
1
Order By: Relevance
“…Alpha/beta T-cell depletion was first applied in children [5]. Indeed, a review summarizing studies in children concluded that there is no clear difference in survival between PTCy and Tcell depletion in haploidentical transplants due to heterogeneity in trials, including patient populations, methodologies and supportive care approaches [13]. In our study in adult patients, we could not detect any significant difference in overall or relapse-free survival between the PTCy and T-cell depletion groups.…”
Section: Resultscontrasting
confidence: 77%
“…Alpha/beta T-cell depletion was first applied in children [5]. Indeed, a review summarizing studies in children concluded that there is no clear difference in survival between PTCy and Tcell depletion in haploidentical transplants due to heterogeneity in trials, including patient populations, methodologies and supportive care approaches [13]. In our study in adult patients, we could not detect any significant difference in overall or relapse-free survival between the PTCy and T-cell depletion groups.…”
Section: Resultscontrasting
confidence: 77%
“…techniques using microbeads conjugated magnetically with monoclonal antibodies, 33 which allows a highly efficient negative selection of alloreactive T-cells similar to TCRαβ+ T-cells depletion, represents a valuable step forward in ex vivo graft manipulation. 34,35 These appoaches guarantee a low risk of GvHD while promoting engraftment, effective infections management and, in leukemia patients, relapse prevention 36,37 by the persistence in the graft of several cell types like Natural Killer Cells (NK-cells) and TCRγδ+ T cells. 38 Similarly, the introduction of PTCy in T-repleted haplo-SCT contributed to the reduced risk of GvHD due to the killing of emerging alloreactive T-cells in the first days after transplant, 39,40 preserving engraftment and immune reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…Haplo-HSCT using T-cell replete grafts constitutes an interesting approach, however, it has to be determined if the use T-cell-repleted grafts results in a stronger GvT-effect. So far none of the different transplantation protocols was superior over the others regarding OS or relapse ( 44 ).…”
Section: Discussionmentioning
confidence: 99%